Utility of acid fermented squid waste silage in diets for the Gangetic koi(Anabas cobojius) - Vikrant M Burad (School of aquaculture and biotechnology, 2016)
Abstract- A feeding trial was conducted for 60 days in indoor circular cement cisterns to evaluate the utilization of acid fermented squid waste as feed ingredient in the diet of Anabas cobojius fingerlings. Three different test diets were prepared by replacing fish meal with either formic acid fermented squid waste @10 % (T1), sulphuric acid fermented squid waste @10% (T2), combination of formic acid fermented squid waste (5%) and sulphuric acid fermented squid waste (5%) (T3), combination of formic acid fermented squid waste (10%) and sulphuric acid fermented squid waste (10%) (T4). The basal diet without acid fermented squid waste served as the control (C). The crude protein level of the diets was maintained at around 30%. Each diet was tested in triplicate, being fed to fishes in a set of three tanks each. The study was conducted in cement cisterns of capacity 300 litre stocking was done with fingerlings of Anabas cobojius @ 10nos. / cistern. Completely randomized design was adopted for the study. Feeding was done @ 5% of body weight twice daily. The water quality parameters in the cisterns were monitored by sampling in 12 days span. Fish growth was also assessed by periodic sampling, the quantity of feed given being readjusted based on the increase in weight. On termination of the study all surviving fishes were collected and their length and weight recorded. Feed ingredients, formulated feeds, were analysed for proximate composition employing standard methods. The present experiment indicate best growth of Anabas cobojius in terms of average weight gain (12.54g), SGR (1.79), FCR (1.58) in diet T1 containing 10% formic acid fermented squid waste than the other groups. Survival rate was good in all the treatments with mean survival value ranging from 83.33% to 100%. The results suggest the possibility of utilizing formic acid fermented squid waste at 10% level in the diets of Anabas cobojius. Further studies on the use of acid fermented squid waste in the diets of Anabas cobojius are recommended.